Biomarkers Associated with Stroke Risk in Atrial Fibrillation - Ioannou, Adam; Papageorgiou, Nikolaos; Falconer, Debbie; Rehal, Onkar; Sewart, Emma; Zacharia, Effimia; Toutouzas, Konstantinos; Vlachopoulos, Charalambos; Siasos, Gerasimos; Tsioufis, Costas; Tousoulis, Dimitris (Current Medicinal Chemistry, 2019)
Background: Atrial fibrillation (AF) is associated with an increased risk of cardioembolic stroke. The risk of cardioembolism is not adequately reduced with the administration of oral anticoagulants, since a number of patients continue to experience thromboembolic events despite receiving treatment. Therefore, identification of a circulating biomarker to identify these high-risk patients would be clinically beneficial. Objective: In the present article, we aim to review the available data regarding use of biomarkers to predict cardioembolic stroke in patients with AF. Methods: We performed a thorough search of the literature in order to analyze the biomarkers identified thus far and critically evaluate their clinical significance. Results: A number of biomarkers have been proposed to predict cardioembolic stroke in patients with AF. Some of them are already used in the clinical practice, such as d-dimers, troponins and brain natriuretic peptide. Novel biomarkers, such as the inflammatory growth differentiation factor-15, appear to be promising, while the role of micro-RNAs and genetics appear to be useful as well. Even though these biomarkers are associated with an increased risk for thromboembolism, they cannot accurately predict future events. In light of this, the use of a scoring system, that would incorporate both circulating biomarkers and clinical factors, might be more useful. Conclusions: Recent research has disclosed several biomarkers as potential predictors of cardioembolic stroke in patients with AF. However, further research is required to establish a multifactorial scoring system that will identify patients at high-risk of thromboembolism, who would benefit from more intensive treatment and monitoring.
Keywords: cardioembolic stroke